A new method for managing multidimensional risks in Natural Gas Pipelines based on non-Expected Utility. (October 2021) - Medeiros, Cristina Pereira; da Silva, Lucas Borges Leal; Alencar, Marcelo Hazin; de Almeida, Adiel Teixeira
Highlights: This paper proposes a Non-EU method to assess multidimensional risks in NGP systems. The MRDU model produce greater assertiveness in the NGP risk prioritization. The new method overcomes the EU violations by using a weighting function. The axiomatic structure of MRDU generalizes the EU approach from MAUT. A numerical application with MRDU evidenced considerably more robust results. Abstract: Enhancing safety and maintaining profitable operations in various types of organizations, including in gas transmission and distribution companies, is a challenging task. Multidimensional risk analysis of Natural Gas Pipelines (NGP) has been carried out in decision-making in order to guide the decision-maker (DM) in managing resource allocation and prioritizing risks in pipeline sections. Although the Literature puts a spotlight on Expected Utility (EU) methods for assessing DM's preferences, the NGP problem is based on the probability of the occurrence of hazard scenarios being small, and yet there being high impacts when a failure occurs. That is why this paper proposes a new multidimensional model for assessing NGP risks: the MRDU model. To the best of our knowledge, there is an absence in the literature of studies on using non-Expected Utility (non-EU) methods. Non-EU is a new approach which is based on Utility Theory. Deviations of utilities are explored and this incorporates contributions from the Rank-Dependent Utility (RDU)-based risk approach. Relevant results are compared and an extensive sensitivity analysis is conducted. Results show that the risk approach based on non-EU gives greater support to the recommendations made to the DM with regard to prioritizing NGP sections.